Abivertinib in patients with T790M‐positive advanced NSCLC and its subsequent treatment with osimertinib. Issue 3 (14th January 2020) - Wang, Hanping; Pan, Ruili; Zhang, Xiaotong; Si, Xiaoyan; Wang, Mengzhao; Zhang, Li
Abstract: Background: Abivertinib is a novel oral, third generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) that overcomes T790M‐induced resistance in non‐small cell lung cancer (NSCLC) patients. Here, we report the results of a complete and detailed clinical data of patients treated with abivertinib at our hospital in a phase I dose escalation/expansion study of abivertinib. Methods: NSCLC patients with the EGFR T790M mutation were orally administered abivertinib (150–300 mg) twice daily for cycles of 28 continuous days and tumor response was assessed. Further data regarding subsequent treatment protocols and survival were collected. Results: A total of 28 NSCLC patients were included. Of the 24 assessable patients, 12 (50%) achieved a partial response (PR), and six (25%) achieved stable disease (SD). Median progression‐free survival (PFS) was 5.9 months (95% confidence interval (CI): 3.259–8.541) and median overall survival (OS) was 17.9 months (95% CI: 11.36–24.5). For salvage therapy in 15 (53.6%) patients after abivertinib, the median PFS following osimertinib treatment was 12 months. The median total treatment duration for the two third‐generation EGFR TKIs was 15.9 months (95% CI: 12.5–19.3). The most frequent abivertinib‐associated adverse effects were elevated hepatic transaminases (10/28, 35.7%) and diarrhea (10/28, 35.7%). Conclusions: Abivertinib is a unique novel third‐generation EGFR TKI with good tolerance and efficacy in EGFR T790M(+) NSCLC patients. For patients with progressive disease after treatment with abivertinib, osimertinib could be an option for subsequent therapy but further studies are required. Key points: Abivertinib is a novel third‐generation EGFR TKI targeting the EGFR T790M mutation Abivertinib is well tolerated and efficacious in T790M‐positive patients Abivertinib has a unique structure, efficacy, and resistance mechanism compared with osimertinib Osimertinib treatment after AC0010 showed a good response